Waste management: what is the choice: land disposal or biofuel - Idris, Azni (Universiti Putra Malaysia Press, 2009)

(untitled)
Many cities in developing Asian countries are facing serious problems in managing their municipal solid wastes as annual waste generation increases in proportion to the rise in population and urbanization. Asian countries with greater rural settings produce more organic waste such as kitchen wastes and less of recyclable items such as paper, metals and plastics. The method of disposing wastes using landfill poses a serious environmental threat which requires innovation and more research has to be carried out to solve this issue. New challenges faced by local authorities are related mainly to finding the best option for managing the problems and costs of collection and disposal of solid wastes in a growing city. With the global scenario of escalating cost of fuel prices, municipal solid waste is seen as a potential resource for our renewable energy project. There is growing interest in the utilization of solid waste as biofuel to produce electricity. Various technologies in converting the waste material into biofuel are made available, which may change the landscape of today’s waste management, from landfill disposal to resource recovery.Biofuel economy has steered our thoughts towards the conversion of such unwanted materials into valuable energy feedstock, which the world is now seriously moving towards. With the emergence of new technologies for conversion of wastes into biofuel, be it biomass or biogas, the options are now very clear. The Biofuel option can be the best strategy as long as our policies are targeted toards achieving sustainable development as the ultimate goal.